2019
DOI: 10.3390/ijms20071554
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p300/CBP-Associated Factor Attenuates Renal Tubulointerstitial Fibrosis through Modulation of NF-kB and Nrf2

Abstract: p300/CBP-associated factor (PCAF), a histone acetyltransferase, is involved in many cellular processes such as differentiation, proliferation, apoptosis, and reaction to cell damage by modulating the activities of several genes and proteins through the acetylation of either the histones or transcription factors. Here, we examined a pathogenic role of PCAF and its potential as a novel therapeutic target in the progression of renal tubulointerstitial fibrosis induced by non-diabetic unilateral ureteral obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 41 publications
7
37
0
Order By: Relevance
“…IL-6 also has been shown to play an important role in cisplatin-induced inflammation [ 50 ]. Consistent with our findings, previous studies have shown that garcinol suppressed cytokine production in lipopolysaccharide-stimulated microglia [ 48 ], IL-1β-treated chondrocytes [ 30 ], and kidneys from mice subjected to unilateral ureteral obstruction [ 51 ]. In addition, we found that administration of garcinol suppressed accumulation of neutrophils and macrophages along with downregulation of chemokines and vascular adhesion molecules.…”
Section: Discussionsupporting
confidence: 93%
“…IL-6 also has been shown to play an important role in cisplatin-induced inflammation [ 50 ]. Consistent with our findings, previous studies have shown that garcinol suppressed cytokine production in lipopolysaccharide-stimulated microglia [ 48 ], IL-1β-treated chondrocytes [ 30 ], and kidneys from mice subjected to unilateral ureteral obstruction [ 51 ]. In addition, we found that administration of garcinol suppressed accumulation of neutrophils and macrophages along with downregulation of chemokines and vascular adhesion molecules.…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress is an imbalance between the oxidation system and the endogenous antioxidant defense system that results in ATP depletion. As described in previous reports, UUO is linked to reduced levels of the antioxidative enzymes SOD1 and Catalase [44,45]. Our findings confirmed these results, as detected by Western blot of in vivo samples and DCFH-DA probe analysis of in vitro samples.…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, NF- κ B, a key factor of inflammatory signaling, could once be phosphorylated and enter into the nucleus, activating the genes of inflammatory and fibrogenic factors. It has been reported that NF- κ B signaling was activated in UUO models, and the blockade of NF- κ B signaling would improve renal fibrosis [ 34 , 35 ]. Our results found significantly elevated protein levels of P65, p-P65, and p-i κ B α and decreased level of i κ B α in UUO rats, whereby hirudin efficiently reversed these changes.…”
Section: Discussionmentioning
confidence: 99%